Do visual fields need to be considered in classification criteria within visually impaired shooting?. (13th August 2021) - Latham, Keziah; Mann, David L.; Dolan, Rebecca; Myint, Joy; Timmis, Matthew A.; Ryu, Donghyun; Frisson, Steven; Allen, Peter M.
ABSTRACT: Classification within the sport of vision impairment (VI) shooting is based upon the athlete's visual function. This study aimed to determine whether more than one class of competition is needed within VI shooting on the basis of visual field loss. Qualification scores of 23 elite athletes were obtained at World Championship events in prone and standing shooting disciplines. Visual field data were obtained from classification data and from assessment at events. A standardized scoring protocol determined whether athletes had function (≥10 dB) or no function (<10 dB) at locations between 0–60 degrees eccentricity along 10 meridia. Visual field function was not associated with shooting performance in prone or standing disciplines (p > 0.05). Having measurable visual field function beyond 30 degrees made no difference to athletes' ability to shoot competitively in prone (p = 0.65) or standing disciplines (p = 0.47), although a potential impact on qualification was observed in the standing discipline. There was no evidence that loss of visual field function at any specific location adversely affected ability to shoot competitively. There is currently no evidence to consider visual fields in classification within prone or standing VI shooting, although further research is needed as the sport grows.